Ferramentas de suporte ao estudo da disciplina de Sistemas Digitais: Carta de Implicações - Barbosa, Sérgio (2007)
The Implication Chart is an algorithm used to simplify Finite State Machines which is a lectured part of the Digital Systems course, under the Engineering Electronics, Telecommunication and Informatics Department responsibility. The result of all the work presented here is an efficient toolused at the project stage of sequential components and useful in the learning support. Developed for Microsoft platforms, it uses Excel and VisualBasic for Applications, as the tool support and programminglanguage respectively. The programming code of the algorithm engine has beengiven double function: used in the tool presented here andintegrates the Mathematical Education Project platform asan engine of exercises resolution. At the end, we hope that this document will transmit theidea that, it’s possible to build useful scenarios in the learning process, with common tools.